An immunization based on node activity. (February 2018) - Nian, Fuzhong; Hu, Chasheng; Yao, Shuanglong; Wang, Longjing; Wang, Xingyuan
Abstract: In this paper, a standard susceptible-infected-recovered-susceptible (SIRS) epidemic model based on the dynamic network model is established. The dynamic network based on the Barabasi–Albert (BA) scale-free network model is constructed, keeping the same total number of edges, adding and deleting edges are operated according to the corresponding node activity level. These operations also can change the node activity. At the same time, a new immunization scheme - "immunization based on node activity" is proposed, in which the nodes with most active be immunized firstly. The propagation situations of random immunization, immunization based on node activity and high-risk immunization are investigated, the influence of some parameters on the density of infected individuals is also analyzed in detail. When the number of immunization nodes is the same, the results show that the effect of immunization based on node activity is the best. Therefore, immunization based on node activity is effective, and it is more feasible in dynamic network.